2005
DOI: 10.4172/1747-0862.1000007
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of methylenetetrahydrofolate reductase 677C>T mutation with coronary artery disease in a Pakistani population

Abstract: Pakistanis belong to the South Asian population which has the highest known rate of coronary artery disease. Folic acid deficiency also appears to be highly prevalent in this population. Methylenetetrahydrofolate reductase (MTHFR) 677C>T polymorphism decreases the activity of this enzyme and can be associated with mild to moderate hyperhomocysteinemia in homozygotes, particularly when there is folic acid deficiency, as well as with coronary artery disease. To assess the value of genotyping the MTHFR 677C>T dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
1
10
0
1
Order By: Relevance
“…In this population the frequency of the TT genotype was more common among patients with coronary artery disease than the control group (Li 2012). Regardless of the results of recent meta-analyses, the role of the C677T polymorphism in the etiopathology of coronary artery disease and myocardial infarction is still controversial, and it has not been observed in some populations (Balogh et al 2012; Iqbal et al 2005). This discrepancy may be related to differences in genetic background in the populations studied or to differences in the selection of patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…In this population the frequency of the TT genotype was more common among patients with coronary artery disease than the control group (Li 2012). Regardless of the results of recent meta-analyses, the role of the C677T polymorphism in the etiopathology of coronary artery disease and myocardial infarction is still controversial, and it has not been observed in some populations (Balogh et al 2012; Iqbal et al 2005). This discrepancy may be related to differences in genetic background in the populations studied or to differences in the selection of patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 ] A study investigated that MTHFR 677CT polymorphism, though associated with homocysteine levels, confers no significant risk of CAD in the Pakistani population. [ 25 ] Limited data are available for other Asian populations, especially Indians. [ 26 – 28 ] Nair et al ,[ 26 ] reported that heterozygosity for thermolabile MTHFR mutation was associated with hyperhomocysteinemia, which could be a risk factor for CAD in the Indian population.…”
Section: Discussionmentioning
confidence: 99%
“…Some groups have been shown to be genetically distinct (Qamar et al, 2002;Mansoor et al, 2004). Data regarding C677T occurrence in Pakistan are almost nonexistent except a few reports describing association of this mutation with primary closedangle glaucoma (Michael et al, 2008) and coronary artery disease (Iqbal et al, 2005). Due to high geographic and social diversity existing in Pakistan (Ahmed and Sirageldin, 1993), we hypothesized a varied prevalence of C677T mutation.…”
Section: Introductionmentioning
confidence: 94%